2022
DOI: 10.3390/nano12142357
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone as a Stabilizer in Synthesis of AgInS2 Quantum Dots

Abstract: A synthesis protocol of polyvinylpyrrolidone-capped AgInS2 quantum dots in aqueous solution is reported. Nanoparticle morphology and chemical composition were studied by means of TEM, XRD, XPS, and FTIR. The obtained quantum dots were luminescent in the visible range. The photoluminescence intensity dependence on the polyvinylpyrrolidone amount was demonstrated. The wavelength of the emission maximum varied with changing the [Ag]:[In] molar ratio. The temperature dependence of the photoluminescence intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In [50], the authors suggested that thiol groups could influence the PL emission properties of aqueous I-III-VI QDs through the transfer of a hole to the redox level of surface-bound disulfides formed via ligand oxidation. In our previous work [21], though, we observed very little narrowing of the PL curve with decreasing temperature for non-thiol (thiol-less) PVP-capped AgInS 2 QDs. It is likely that the stabilization mechanism of these QDs is based on the interaction of oxygen from PVP with the QD surface.…”
Section: Temperature-dependent Photoluminescencementioning
confidence: 53%
See 1 more Smart Citation
“…In [50], the authors suggested that thiol groups could influence the PL emission properties of aqueous I-III-VI QDs through the transfer of a hole to the redox level of surface-bound disulfides formed via ligand oxidation. In our previous work [21], though, we observed very little narrowing of the PL curve with decreasing temperature for non-thiol (thiol-less) PVP-capped AgInS 2 QDs. It is likely that the stabilization mechanism of these QDs is based on the interaction of oxygen from PVP with the QD surface.…”
Section: Temperature-dependent Photoluminescencementioning
confidence: 53%
“…Aqueous techniques become even more relevant in the case of I-III-VI nanocrystals, which are typically synthesized in nonpolar media employing aliphatic thiols as coordinating ligands, resulting in the strong coordination of surface groups and hindering ligand exchange. The synthesis of ternary and quaternary QDs in aqueous medium can be achieved using a various types of capping ligands such as thiols [15,16], amino-acids [17][18][19], polymers [20,21], etc., providing excellent long-term colloidal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PVP had good water solubility and biocompatibility. , PVP was employed to control the growth of MOF crystals, regulate nanoparticle size and shape, and avoid self-aggregation . The ZIF-8 morphology was changed by adding different surfactants, including PVP, poly­(ethylene glycol), tannin (TA), cetyltrimethylammonium bromide (CTAB), and sodium dodecyl sulfate .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this study, AgIn standard card JCPDS 25-1330 [29] . By comparing the characteristic peaks AgInS 2 -SnIn 4 S 8 at different ratios, AgInS 2 -SnIn 4 S 8 (1:0.5) has the best crystalline structure and is expected to exhibit the best photocatalytic activity in multimodal photocatalytic performance studies.…”
Section: Introductionmentioning
confidence: 99%